Cardiac catheterisation by the Judkins technique as an outpatient procedure. Issue 6677 (1st April 1989) - Oldroyd, K. G.; Phadke, K. V.; Phillips, R.; Carson, P. H.; Clarke, M.; Davis, J. A.
Abstract : OBJECTIVE–To assess the safety and cost benefit of left heart catheterisation by a modified Judkins technique performed as a day patient procedure. DESIGN–Review study of case notes of consecutive patients examined by the procedure over three years (January 1984 to December 1986). SETTING–Outpatient referrals in a regional cardiac centre within a district general hospital. PATIENTS–Nine hundred patients aged 18-76 (mean 54) selected at a previous clinic as suitable for the procedure. MAIN RESULTS–Eight hundred and fifty patients (94.4%) were discharged home on the day of the procedure. Forty others (4.4%) could not be discharged owing to complications during or just after the procedure. Of these patients, two died (0.2%), six suffered a myocardial infarction (0.7%), and two had major vascular complications. The remaining 30 patients were admitted because of chest pain without infarction (10 cases), minor vascular incidents (six), haemorrhage at the puncture site (five), arrhythmia (four), pulmonary oedema (three), and contrast reaction (two). Ten patients were admitted for either urgent coronary artery bypass grafting or social reasons. CONCLUSIONS–Cardiac catheterisation is safe as an outpatient procedure in most cases. Beds are spared and roughly 35, 000 pounds is saved for every 500 procedures performed.